Rechallenge in idiosyncratic drug-induced liver injury: An analysis of cases in two large prospective registries according to existing definitions. - Pinazo-Bandera, José M.; Niu, Hao; Álvarez-Álvarez, Ismael; Medina-Cáliz, Inmaculada; Del Campo-Herrera, Enrique; Ortega-Alonso, Aida; Robles‑Diaz, Mercedes; Hernandez, Nelia; Parana, Raymundo; Nunes, Vinicius; Girala, Marcos; Bessone, Fernando; et al. (Elsevier, 2024)
Introduction: Data on positive rechallenge in idiosyncratic drug-induced liver injury (DILI) are scarce. We aim to analyse the clinical presentation, outcome and drugs associated with positive rechallenge in two DILI registries. Methods: Cases from the Spanish and Latin American DILI registries were included. Demographics, clinical characteristics and outcome of cases with positive rechallenge according to CIOMS/RUCAM and current definitions were analysed. Results: Of 1418 patients with idiosyncratic DILI, 58 cases had positive rechallenge (4.1%). Patients with positive rechallenge had shorter duration of therapy (p=0.001) and latency (p=0.003). In patients with rechallenge, aspartate transaminase levels were increased (p=0.026) and showed a prolonged time to recovery (p=0.020), albeit no differences were seen in terms of fatal outcomes. The main drug implicated in rechallenge was amoxicillin-clavulanate (17%). The majority of re-exposure events were unintentional (71%). Using both existing definitions of positive rechallenge, there were four cases which exclusively fulfilled the current criteria and five which only meet the historical definition. All cases of positive rechallenge, irrespective of the pattern of damage, fulfilled the criteria of either alanine transaminase (ALT) ≥3 times the upper limit of normal (ULN) and/or alkaline phosphatase (ALP) ≥2 times ULN. Conclusions: Episodes of rechallenge were characterised by shorter duration of therapy and latency, and longer time to resolution, but did not show an increased incidence of fatal outcome. Based on our findings, ALT ≥3 times ULN and/or ALP ≥2 times ULN, regardless of the pattern of damage, is proposed as a new definition of rechallenge in DILI.
Keywords: Hígado - Heridas y lesiones; Hepatotoxicidad; Drug-induced liver injury; Hepatotoxicity; Positive rechallenge; Acute liver failure